Relationship between the adherence to diet and nutritional education in patients with dialysis at the General Hospital of Atlacomulco and the General Hospital of San Felipe del Progreso, State of Mexico. - Chávez-Becerril, Graciela Berenice (2019)
Objetive: to determine the association between adherence to the diet and nutritional education in patients with dialysis treatment. Material and Methods: Cross-sectional descriptive study in patients with Chronic Kidney Disease on dialysis treatment ≥6 months, who have previously received nutritional education. The State of Nutrition was evaluated by means of the Subjective Global Assessment (SGA), skinfolds (tricipital and subescapular), dry weight and height (according to the parameters established by the International Society for Advances of Kinanthropometry); nutritional knowledge and adherence through the Knowledge and Adherence to The Therapeutic Regimen Survey; quality of life through the KDQOL-SF ™ instrument. Results: 85 patients were included, 46 (54%) men and 39 (46%) women with an average age of 42 ± 17 years and a mean time with dialysis treatment 3 ± 1.96 years. 58% of the patients did not have adherence to the diet. However, 89% of patients adhered to the sodium restriction recommendation, while 59% adhered to fluid intake. According to the VGS, 58% of the patients presented mild/moderate malnutrition, however, 71% had average fat according to the sum of the skinfolds and 67% presented a normal nutritional status determined by Body Mass Index (BMI). Conclusions: no significant difference in adherence to dietary treatment was observed in those patients who have nutritional knowledge compared to those who do not.